Intestinal epithelial cell transported TLR2 ligand stimulates Ly6C+ monocyte differentiation in a G-CSF dependent manner - Hiemstra, Ida H.; Vrijland, Kim; Hogenboom, Marye M.; Bouma, Gerd; Kraal, Georg; den Haan, Joke M.M. (Immunobiology (1979), 2015)
Microflora-induced TLR signaling in the intestinal epithelium is essential for a proper intestinal barrier function. Because of the close interactions of this epithelial layer with underlying mononuclear phagocytes, we hypothesized that epithelial TLR signaling may affect the differentiation of myeloid cell populations. In in vitro cultures we observed that colonic epithelial monolayers actively transported TLR2 ligands towards their basolateral side. The transported TLR2 ligands strongly stimulated the development of Ly6C+ monocytes, while dendritic cell differentiation was inhibited. The TLR2 effect on monocyte and dendritic cell differentiation was mediated by the production of G-CSF. Mice lacking TLR signaling and mice that were treated with antibiotics showed decreased numbers of Ly6C+ monocytes in bone marrow and spleen, which points to a role for microbial derived TLR-ligands in the homeostasis of Ly6C+ monocytes. In conclusion, our results indicate that TLR ligands that are transported by intestinal epithelial cells stimulate Ly6C+ monocyte development and suggest that this process may be involved in the maintenance of systemic Ly6C+ monocyte numbers.